The role of physiotherapy interventions in the management of temporomandibular joint ankylosis: a systematic review and meta-analysis - Ravinder S. Saini; Mohammed Ibrahim; Mohasin Abdul Khader; Masroor Ahmed Kanji; Seyed Ali Mosaddad; Artak Heboyan (Head & Face Medicine, 2024)
Abstract Background The main aim of this systematic review and meta-analysis was to identify peer-reviewed scholarly journal articles reporting the significance of physiotherapy interventions in managing TMJ ankylosis. In addition, this study aimed to critically appraise the existing evidence on the prevalence and clinical presentation, physiotherapy intervention approaches, efficacy of physiotherapy interventions, adverse effects, and safety of physiotherapy interventions in TMJ ankylosis management. Methods An all-inclusive literature search was conducted using the PubMed, Google Scholar, and Scopus electronic databases. The researchers screened the potential articles and assessed for eligibility based on the reported inclusion and exclusion criteria. The quality evaluation tool for observational cohort and cross-sectional studies developed by the National Institutes of Health (NIH) and the Cochrane Collaboration's Risk of Bias Tool were used to assess the quality of the included studies. Researchers also comprehensively analyzed the data, reported the results, and discussed them according to the predominant themes. Results The primary electronic database search yielded 409 articles, of which 25 were included in this review. A secondary search was conducted from citations of the included studies, yielding 74 articles, of which six were included in the study. A significantly higher prevalence of bony ankylosis than fibrous ankylosis, with an overall effect size of p < 0.00001. In addition, there were significantly more unilateral than bilateral presentations with an overall effect size of p < 0.00001. Moreover, there were 78 reported complications out of 245 subjects according to five included studies demonstrating a significant effect size with p = 0.001 following the treatment protocols. Conclusion This study highlighted the prevalence of bony ankylosis in temporomandibular joint ankylosis, emphasizing its impact on patients' well-being. On the other hand, the results show that physiotherapy is essential to optimize postoperative outcomes and minimize adverse events such as re-ankylosis. Practitioners and healthcare professionals must monitor postoperative recovery and ensure strict adherence to physiotherapy protocols for optimal outcomes.